Lipids and Membrane Lateral Organization - Sonnino, Sandro; Prinetti, Alessandro (Frontiers in Physiology, 2010)
Shortly after the elucidation of the very basic structure and properties of cellular membranes, it became evident that cellular membranes are highly organized structures with multiple and multi-dimensional levels of order. Very early observations suggested that the lipid components of biological membranes might be active players in the creations of these levels of order. In the late 80’s, several different and diverse experimental pieces of evidence coalesced together giving rise to the lipid raft hypothesis. Lipid rafts became enormously (and, in the opinion of these authors, sometimes acritically) popular, surprisingly not just within the lipidologist community (who is supposed to be naturally sensitive to the fascination of lipid rafts). Today, a PubMed search using the key word “lipid rafts” returned a list of 3767 papers, including 690 reviews (as a term of comparison, searching over the same time span for a very hot lipid-related key word, “ceramide” returned 6187 hits with 799 reviews), and a tremendous number of different cellular functions have been described as “lipid raft-dependent”. However, a clear consensus definition of lipid raft has been proposed only in recent times, and the basic properties, the ruling forces, and even the existence of lipid rafts in living cells have been recently matter of intense debate. The scenario that is gradually emerging from the controversies elicited by the lipid raft hypothesis emphasize multiple roles for membrane lipids in determining membrane order, that encompasses their tendency to phase separation but are clearly not limited to this. In this review, we would like to re-focus the attention of the readers on the importance of lipids in organizing the fine structure of cellular membranes.